Full list of metrics, indicators, and health-related outcomes used in PAICE rapid literature - Rachel Juel (11796266) (2025)
This document supplements a protocol published for a rapid review on Wellcome Open Research. The main research question was for the rapid literature review of climate change adaptation and mitigation, health-related indicators was: In what ways do health-related climate adaptation and mitigation indicators intersect, and how can these intersections guide the design of integrated monitoring frameworks. Following from it, the main research aim was to identify and characterize cross-overs between health-related climate adaptation and mitigation indicators, in order to inform the development of integrated monitoring frameworks that better capture health co-benefits and trade-offs of climate policy. This rapid review was conducted utilising a multi-layered search strategy, with the foundational layer of the search built from established indicator sets and additional enhancement layers derived from evidence synthesis resources. Foundation Layer: UKHSA Established Indicator Sets The search was first grounded in published climate-health indicator frameworks from the UKHSA Scoping Review and HECC Report indicators, which provide the most up to date inventory of adaptation and health indicators assessed within the UK context. These indicators are primarily adaptation-focused in context, and as such, an additional enhancement layer comprising published and unpublished evidence syntheses is layered upon this foundation layer. Enhancement Layer: Evidence Synthesis Resources To enhance the mitigation indicators included in our search, we include exposures from known health-impact pathways and metrics recommended for tracking the health co-benefits of net-zero actions: Pathfinder Exposure Pathways: this review leveraged the Pathfinder umbrella review's synthesis of mitigation actions with documented health co-benefits. This review documented health-related mitigation exposure pathways which informed search and screening stages of this literature review. WinWindow Metrics: This review utilized the unpublished analysis of UK net-zero co-benefits and potential exposure and outcome metrics (personal communications with Sarah Whitmee, Principal Investigator). These metrics were used in the search and screening of the literature review. The full list of metrics, indicators, and health-related outcomes used in this rapid literature review is published here.